An Integrated Testing Strategy for Ecotoxicity (ITS‐ECO) Assessment in the Marine Environmental Compartment using Mytilus spp.: A Case Study using Pristine and Coated CuO and TiO2 Nanomaterials. (11th April 2022) - Connolly, Mona; Little, Simon; Hartl, Mark G. J.; Fernandes, Teresa F.
Abstract: An integrated testing strategy for ecotoxicity assessment (ITS‐ECO) was developed to aid in the hazard and fate assessment of engineered nanomaterials (ENMs) deposited in marine environments using the bivalve Mytilus spp. as a test species. The ENMs copper(II) oxide (CuO) and titanium dioxide (TiO2 ), either in pristine form (core) or with functionalized coatings (polyethylene glycol [PEG], carboxyl [COOH], and ammonia [NH3 ]) were selected as case study materials based on their production levels and use. High‐throughput in vitro testing in Tier 1 of the ITS‐ECO revealed CuO ENMs to elicit cytotoxic effects on lysosomes of hemocytes of mussels, with the hazard potential CuO PEG > CuO COOH > CuO NH3  > CuO core, whereas TiO2 ENMs were not cytotoxic. Genotoxicity in hemocytes as well as gill cells of mussels following in vivo exposure (48 h) to CuO ENMs was also seen. Longer in vivo exposures in Tier 2 (48 h–21 days) revealed subacute and chronic oxidative effects for both CuO and TiO2 ENMs, in some cases leading to lipid peroxidation (core TiO2 ENMs). In Tier 3 bioaccumulation studies, distinct patterns of uptake for Cu (predominantly in gills) and Ti (predominantly in digestive glands) and between the different core and coated ENMs were found. Clear NM‐specific and coating‐dependent effects on hazard and fate were seen. Overall, using a tiered testing approach, the ITS‐ECO was able to differentiate the hazard (acute, subacute, and chronic effects) posed by ENMs of different compositions and coatings and to provide information on fate for environmental risk assessment of these ENMs. Environ Toxicol Chem 2022;41:1390–1406. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Framework for ecotoxicity testing of engineered nanomaterials (ENMs) using a marine compartment‐specific Integrated testing strategy (ITS‐ECO) and the marine bivalve mussel Mytilus spp.